Cam mechanisms based on a double roller translating follower of negative radius. (January 2016) - Sanmiguel-Rojas, E.; Hidalgo-Martínez, M.
Abstract: Constant-breadth cam mechanisms are characterized by the fact that the closure of the cam-follower contact is guaranteed thanks to the geometry and, therefore, auxiliary elements as springs are not necessary. On the other hand, cam mechanisms with a negative radius roller follower allow designing simple machines exerting remarkably high forces when the space is restricted. This work proposes a new constant-breadth cam mechanism with a double roller translating follower of negative radius. The cam profile is designed with an optimizing method based on Bézier curves. Highlights: A new form-closed cam mechanism is analyzed kinematically. It is based on a double roller follower of negative radius. It is found the maximum of the follower lift avoiding the undercutting. The sliding velocity is calculated in the particular case of sliding followers.